Complicities A theory for subjectivity in the psychological humanities - Distiller, Natasha (Palgrave Studies in the Theory and History of Psychology, 2022)
This Open Access book offers a model of the human subject as complicit in the systems that structure human society and the human psyche which draws together clinical research with theory from both psychology and the humanities to advance a more social just theory and practice. Beginning from the premise that we cannot separate ourselves from the systems that precede and formulate us as subjects, the author argues that, in reckoning with this complicity, a model of subjectivity can be created that moves beyond binaries and identity politics. In doing so, the book examines how we might develop a more socially just psychological theory and practice, which is both systems work and intra-psychological work. In bringing together ways of thinking developed in the humanities with clinical psychotherapeutic practice, this book offers one interdisciplinary take on key questions of social and emotional efficacy in action-oriented psychotherapy work.